Остров Незнайки - Носов Игорь Петрович (Самовар, 2002)
Экземпляры: ф.22 (20181025) / Инвентарный номер: 58712 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 84 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4